On-surface synthesis of metal–organic frameworks: the critical role of the reaction conditions. Issue 20 (20th February 2023) - Ruiz del Árbol, Nerea; Sánchez-Sánchez, Carlos; Martínez, José I.; Rodríguez, Luis; Serrate, David; Verdini, Alberto; Floreano, Luca; Jacobson, Peter; Grill, Leonhard; Martín-Gago, José A.; López, María F.
Abstract : Kinetics versus thermodynamics: their interplay determines the formation of Kagome or honeycomb metal–organic networks from para -aminophenol on Cu(111). Abstract : Two different metal–organic frameworks with either a honeycomb or Kagome structure were grown on Cu(111) using para -aminophenol molecules and native surface adatoms. Although both frameworks are made up from the same chemical species, they are structurally different emphasizing the critical role being played by the reaction conditions during their growth. This work highlights the importance of the balance between thermodynamics and kinetics in the final structure of surface-supported metal–organic networks.